Penerapan Pungutan Pajak Dan Zakat Menurut Konsep Islam Di Indonesia - -, Arif Awal; Faidul Adzim; Cut putri ikhtiar arta; Nur wahyuni syafar; Risky Amelia (Indonesian Journal of Research in Economy, 2023)
The aim of this research is to explore the role and impact of zakat in the economic realm. The research method applied is library research, which combines data from various sources, including books and previous research reports. The results of this research show that the performance of tax officers plays an important role in ensuring the fulfillment of tax payment obligations by taxpayers, while funds for zakat fundraising come from five groups that are required to pay zakat, both for zakat fitrah and zakat maal. Humans, as caliphs on earth, have the responsibility to earn a living in a halal way, avoiding unjust and false actions. Islam recognizes the right to private property without restriction, but prohibits the acquisition of wealth by illegal and immoral means. However, other people's rights are still protected in personal property through the payment of zakat, infaq and sadaqah, in accordance with sharia principles. With significant growth, zakat has the potential to become a significant economic and social instrument for Muslims, and its position is equivalent to income tax paid to the state. The integration of zakat and taxes, if regulated in clear legal concepts and regulations, is believed to be able to advance the Indonesian economy. Fiscal policy, which influences the State Revenue and Expenditure Budget (APBN), can create controversy and various questions because it combines two things that are substantially different. This thesis examines the impact of knowledge about taxes, knowledge about zakat, and tax compliance of Muslim taxpayers, focusing on the direct and indirect influence between tax knowledge, knowledge of zakat, and tax compliance of Muslim taxpayers.